2016
DOI: 10.1039/c6cy00257a
|View full text |Cite
|
Sign up to set email alerts
|

Spatial effects of oxovanadium-immobilized mesoporous silica on racemization of alcohols and application in lipase-catalyzed dynamic kinetic resolution

Abstract: The nano-scale pores of mesoporous silica and their polar environment accelerate the racemization to make the lipase/oxovanadium combo-catalysed DKR applicable to a wider range of alcohols.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
34
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 63 publications
1
34
0
Order By: Relevance
“…They were used in tandem with various lipases to deracemize a wide range of functionalized secondary alcohols, including aliphatic, allylic alcohols, chlorohydrins, diols, homoallylic alcohols, and N -heterocyclic 1,2-aminos alcohols, α -hydroxyl ketones with excellent yields and enantiomeric excess ( ee ) (Verho et al, 2015). Besides the above-mentioned homogeneous catalysts, heterogeneous acids, zeolites (Magadum et al, 2017; Xu et al, 2017) and vanadium based mesoporous silica (Sugiyama et al, 2016) were also reported as racemization catalysts of secondary alcohols. The DKR of amines is more challenging due to a lack of efficient racemization catalysts.…”
Section: Tandem Chemo-enzymatic Reactionsmentioning
confidence: 99%
“…They were used in tandem with various lipases to deracemize a wide range of functionalized secondary alcohols, including aliphatic, allylic alcohols, chlorohydrins, diols, homoallylic alcohols, and N -heterocyclic 1,2-aminos alcohols, α -hydroxyl ketones with excellent yields and enantiomeric excess ( ee ) (Verho et al, 2015). Besides the above-mentioned homogeneous catalysts, heterogeneous acids, zeolites (Magadum et al, 2017; Xu et al, 2017) and vanadium based mesoporous silica (Sugiyama et al, 2016) were also reported as racemization catalysts of secondary alcohols. The DKR of amines is more challenging due to a lack of efficient racemization catalysts.…”
Section: Tandem Chemo-enzymatic Reactionsmentioning
confidence: 99%
“…However, most are expensive, not eco‐friendly or not readily available and, in some cases, they require conditions that are harmful to lipases, such as high temperatures or the presence of strong bases. Therefore, substantial effort has been devoted to developing biocompatible and more environmentally benign racemization catalysts, such as solid acids, zeolites and vanadium compounds …”
Section: Introductionmentioning
confidence: 99%
“…However, depending on the reaction time and oxovanadium catalyst activity, both the metal and biocatalyst can be deactivated due to catalyst interactions. To overcome this limitation, the Akai group used an immobilization strategy in which the vanadium catalyst was incorporated into a mesoporous silica matrix (V–MPS), allowing low catalyst loading (1 mol%) and high recyclability . In the DKR of rac ‐1‐phenylbut‐2‐en‐1‐ol, this V–MPS racemization catalyst presented excellent recyclability (over six reaction cycles), affording the ( R )‐product in quantitative chemical yield and complete optical purity .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Multistep one-pot processes represent a smart synthetic concept that increases the overall preparation efficiency by decreasing the number of isolation and purification steps, in addition to allowing a reduction in the quantities of organic solvents and reagents required for each step. 1 Catalysis plays a central role in realizing such one-pot processes because catalytic transformations can avoid the generation of stoichiometric byproducts. Therefore, the combined use of multiple catalysts, each of which conducts a different reaction, in a single flask will further amplify the overall transformation efficiency.…”
mentioning
confidence: 99%